Strategic flexibility in a male-dominated occupation: women software engineers in China. - Li, Xiaotian (Journal of Gender Studies, 2023)
This article builds on a rich literature on the gender gap in software engineering. It further contextualizes the gendering of development work in the Chinese high-tech industry, especially the prevalent overwork norm. The perpetuation of male ascendency is achieved through the gendered hierarchization of subspecialties in software engineering and the embodiment of the geek culture. Nevertheless, women show their resilience and strength in navigating their careers in this male-dominated occupation. This article reveals female programmers' strategies: flexible assimilation, flexible embodiment, and flexible career development. By this strategic flexibility, the article highlights women's agency in tactically negotiating gender rules and transgressing gender boundaries in a male-dominated occupation.